Efeito do biochar e de águas salinas sobre o crescimento e nutrição do milho e na salinidade do solo - Costa, Maria Eugênia da (Universidade Federal Rural do Semi-Árido, 2017)
Due to the low yield of maize in the state of Rio Grande do Norte, attributed to factors like climate and degradation of water and soil, including salinization, the present work aimed to evaluate the effect of biochar application in mitigating effects of water salinity in different soils of the western region of this estate cultivated with maize. With this aim, four doses of biochar (0, 0.5, 1.0, and 1.5%) and waters of three salinity levels (0.57, 2.65, and 4.50 dS m-1) were applied in three types of soils (Ultisol, Inceptisol, and Fluvent). Three trials were carried out, one for each soil type contained in columns, in an entirely randomized design with four replications in the western campus of the Federal Rural University of the Semi-Arid, UFERSA, located in the municipality of Mossoró, RN, Brazil. The following determinations were performed after 40 days of maize emergence: shoot dry matter of maize and its contents of nitrogen, phosphorus, potassium, calcium and magnesium, plus pH and electrical conductivity of the soil saturation extract (ECse). Data were submitted to variance analysis and regression analysis. The benefit of biochar in mitigating the effect of water salinity on shoot dry mass of maize was observed in the Ultisol and Fluvent soils, in the last when water of medium salinity was applied. Application of biochar along with saline waters improved nutrient absorption by maize plants, but this benefit was dependent on soil type and dose of biochar. In general, the increase in water salinity level was followed by an increase in ECse and a decrease in pH. Application of biochar caused decrease on CEes when the two saline waters were applied, only in the Inceptisol. Overall, increase in the dose of biochar caused increase in soil pH
Keywords: Zea mays L.; Salinidade; Manejo do solo; Carvão vegetal; Zea mays L.; Soil salinity; Soil management; Charcoal; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO